Effects of the pesticide Furadan on traits associated with reproduction in wild potato species - Rio, A. del; Bamberg, J.; Centeno Diaz, R.; Salas, A.; Roca, W.; Tay, D. (Scientific Research Publishing, Inc., 2012)
Natural populations of wild potato species are the backups for the diversity held in genebanks for research and breeding. Some potato species are known to grow in close proximity to cultivated fields, thus are potentially impacted by human activity, including exposure to pesticides. The present study tested the effects of a common pesticide on reproductive traits of potatoes known to grow in or near pesticide-treated fields in central Peru. Furadan? 4F, an insecticide— nematicide (common name = carbofuran) was applied at two different rates to populations representing 15 wild potato species in a greenhouse environment in Peru. Flowering duration of these populations was usually significantly reduced in comparison to a water control, and in a few cases, percent viable pollen also was. These findings suggest that agrichemicals may be having unintentional effects on wild potato populations in ways that could compromise their genetic diversity.